O17.1 Increased HIV Prevention Programme Coverage and Decline in HIV Prevalence Among Female Sex Workers in South India. (13th July 2013) - Alary, M; Banandur, P; Rajaram, S P; Thammattoor, U K; Thomas, T; Mainkar, M K; Paranjape, R; Adhikary, R; Duchesne, T; Ramesh, B M
Abstract : Objectives: As one way of assessing the impact of Avahan, the India AIDS Initiative of the Bill & Melinda Gates Foundation, we examined the association between HIV prevention programme indicators and changes in HIV prevalence among female sex workers (FSWs) between 2006 and 2010. Methods: HIV prevalence among FSWs was measured in two large surveys (2006 and 2010) across 24 districts in south India (n∼11, 000 per round). A random-effect multilevel logistic regression analysis was performed using HIV as the outcome, with individual independent variables (from both surveys) at level 1 and district-level FSW-specific programme indicators (from the Avahan computerised monitoring system) and contextual variables (from Indian government datasets) at level 2. Program indicators included their 2006 value, the difference in their values between the surveys, and the interaction between the latter and study round. The analysis also controlled for baseline HIV prevalence and its interaction with study round. Results: HIV prevalence among FSWs decreased from 17.0% (round 1) to 14.2% (round 2; p < 0.001). The odds ratio (OR) of the interaction term between the difference in programme coverage (% of FSWs contacted by the programme in a given year) and the survey round was 0.995 (p = 0.006), indicating that increased coverage was significantly associated with the decline in HIV prevalence between rounds. ORs comparing HIV prevalence between rounds varied with the level of increase in coverage and were statistically significant with coverage increase ≥ quartile (Q) 1: OR = 0.85 at Q1, 0.78 at Q2, 0.66 at Q3 and 0.51 at Q4. Conclusions: These findings suggest that increased programme coverage was associated with declining HIV prevalence among FSWs covered by the Avahan programme. The triangulation of our results with those from other approaches used in evaluating Avahan suggests a major impact of this intervention on the HIV epidemic in southern India.